Celebrating the Past, Present, and Future of NIDDK-Supported Research Centers Focused on Diabetes, Endocrinology, and Metabolic Diseases - Silva, Corinne M; Thornton, Pamela L; Artis Dickerson, Shavon; Eggerman, Thomas L; Laughlin, Maren R; Wallace, Julie A; Hanlon-Tilghman, Mary C; Cefalu, William T (Diabetes (New York, N.Y.), 2025)
This year marks the 75th anniversary of the National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) of the National Institutes of Health. NIDDK's long history of research and innovation includes support of four types of collaborative research centers focused on diabetes, endocrinology, and metabolic diseases. The Diabetes Research Centers promote basic and clinical diabetes research, while the Centers for Diabetes Translation Research conduct diabetes research across the translation science spectrum. The Mouse Metabolic Phenotyping Center (MMPC)-Live program provides the research community with standardized phenotyping services for mouse models of diabetes and obesity, and the Cystic Fibrosis Research and Translation Centers advance basic, preclinical, and clinical research for cystic fibrosis. These centers have evolved over time in response to new scientific opportunities and to expand their reach to be an asset to the larger scientific community. Looking to the future, NIDDK will continue to ensure that these centers enhance the research community, foster novel and synergistic scientific collaborations, and promote career development of scientists in the early stages of their careers. We will also ensure that our centers align with NIDDK's goal of improving health outcomes for all people with and at risk for diseases, within our mission. NIDDK's research centers focused on diabetes, endocrinology, and metabolism serve broad communities of investigators and address existing research gaps to propel scientific progress. The Diabetes Research Centers support basic and clinical research, and the Centers for Diabetes Translation Research support research across the translation science spectrum. The MMPC-Live program provides phenotyping services for mouse models of diabetes and obesity, and the Cystic Fibrosis Research and Translation Centers advance basic, preclinical, and clinical research for cystic fibrosis. Future goals for the centers include fostering novel and synergistic scientific collaborations, as well as continuing to promote career development.